(untitled) (Biological Sciences - PJSIR, 2018)
Role of rangelands in the livelihoods improvement of rural communes. is pivotal, through animal rearing, obtaining versatile products and services. Rangelands play key role in maintenance of agro- ecosystem and preservation of biodiversity in the country by improving infiltration rate, leading thereby a sustainable water flow in the down streams and reducing soil erosion. However, due to increased population pressure there is analogous increase in the demand for food, forage and other resources. In addition rangelands provide wildlife and fish habitat and recreation spots. Keeping in view the current global climate change scenario the government has given high priority to rangelands management, hence the concentration of the politicians and policy makers is to focus on the sustainable rangeland development and management. The article deals first with the importance of range management, then discusses rangelands problems of Pakistan, causes of degradation of rangelands, human factors contributing to range degradation and finally recommendations are discussed.